Light-Modulated Responses of Growth and Photosynthetic Performance to Ocean Acidification in the Model Diatom Phaeodactylum tricornutum - Li, Yahe; Xu, Juntian; Gao, Kunshan; 徐军田; 高坤山 (PUBLIC LIBRARY SCIENCE, 2014)
National Basic Research Program of China [2011CB200902]; National Natural Science Foundation [41120164007]; Program for Changjiang Scholars and Innovative Research Team [IRT0941]; SOA [GASI-03-01-02-04]; China-Japan collaboration project from MOST [S2012GR0290] Ocean acidification (OA) due to atmospheric CO2 rise is expected to influence marine primary productivity. In order to investigate the interactive effects of OA and light changes on diatoms, we grew Phaeodactylum tricornutum, under ambient (390 ppmv; LC) and elevated CO2 (1000 ppmv; HC) conditions for 80 generations, and measured its physiological performance under different light levels (60 mu mol m(-2) s(-1), LL; 200 mu mol m(-2) s(-1), ML; 460 mu mol m(-2) s(-1), HL) for another 25 generations. The specific growth rate of the HC-grown cells was higher (about 12-18%) than that of the LC-grown ones, with the highest under the ML level. With increasing light levels, the effective photochemical yield of PSII (F-v'/F-m') decreased, but was enhanced by the elevated CO2, especially under the HL level. The cells acclimated to the HC condition showed a higher recovery rate of their photochemical yield of PSII compared to the LC-grown cells. For the HC-grown cells, dissolved inorganic carbon or CO2 levels for half saturation of photosynthesis (K-1/2 DIC or K-1/2 CO2) increased by 11, 55 and 32%, under the LL, ML and HL levels, reflecting a light dependent down-regulation of carbon concentrating mechanisms (CCMs). The linkage between higher level of the CCMs down-regulation and higher growth rate at ML under OA supports the theory that the saved energy from CCMs down-regulation adds on to enhance the growth of the diatom.